한국 고등학생들의 영어 듣기, 읽기 시험 불안 및 정의적 전략 - 최은경(Eun Kyung Choi); 김성연(Sung Yeon Kim) (영어학, 2022)
This study examined Korean high school students’ anxiety and their affective strategy use in taking English listening and reading tests. For the purpose of the study, existing questionnaires from Kim (2002), Saito et al. (1999), and Oxford (1990) were adapted so that the items could measure listening and reading test anxiety, and affective strategy with reference to test-taking situations. For data collection, Korean high school students (n=123) completed the questionnaires, after solving four listening and four reading test items sampled from previous Korean SATs and mock exams. The study found that the students experienced highest levels of anxiety when they could not comprehend the first sentence in listening, and when they had to solve many reading items within a short period of time. It is notable that regardless of skill areas, options presented in English was most anxiety-provoking from learner perspectives. The students’ listening test anxiety and reading test anxiety differed according to learner proficiency, with low proficiency learners experiencing higher levels of anxiety. In terms of strategy use, the students were not so active in employing affective strategies, and in a comparison of high- and low-level students, the former group was found to use affective strategies more frequently than their counterpart. KCI Citation Count: 0